Identification of antibacterial constituents from Rhododendron simsii Planch with an activity-guided method - Lai, Yongji; Zhong, Yu-Ting; Liang, Yu; Chen, Wei-Chen; Liao, Qiuyan; Li, Mu; Han, Pan; Cai, You-Sheng; Wang, Fuqian (Frontiers in Pharmacology, 2024)
Bacterial infections and antibiotic resistance pose significant public health challenges globally, natural products serve as valuable sources for discovering antimicrobial agents. Rhododendron simsii Planch, a folk medicine is used traditionally to treat various inflammatory diseases. Here, we focuses on the investigation of antibacterial metabolites derived from R. simsii Planch, and rhodosimsiin A (1), bearing an 1,5-seco-1,6 and 3,6-epoxy grayanane diterpene skeleton, representing a novel 5/6/7/6/5 pentacyclic ring system, and 3β,16α-dihydroxy-6β-ethoxy-14β-acetoxy-grayan-1(5)-ene-10-one (4) represents the first example of a degradation of C-20 and the carbonylation in C-10 diterpenoid, together with two new grayanane diterpenes (2−3), three new triterpenes (13−15), and known analogues (5−12, 16−30) were isolated from the leaves of R. simsii Planch with bioassay-guided method. Their structures were elucidated by comprehensive spectroscopic analyses and absolute configurations were established by single crystal X-ray diffraction and calculated ECD spectra. Compounds 14, 15, 18, 20, 27, 28 and 30 exhibited potent antibacterial activity with MIC50 of 1.4–24.3 μg/mL against Staphylococcus aureus. The findings of this research indicate that secondary metabolites derived from R. simsii Planch are promising natural antimicrobial candidates.